Successful embolization of ileal conduit stomal varices with N-butyl cyanoacrylate via a recanalized paraumbilical vein - Yasuyuki Onishi, MD; Hiroyuki Kimura, MD, PhD; Mitsunori Kanagaki, MD, PhD; Shojiro Oka, MD; Genki Fukumoto, MD; Tomoaki Otani, MD; Naoko Matsubara, MD; Kazuna Kawabata, MD, PhD; Tomihiko Yasufuku, MD, PhD; Yuji Yamada, MD, PhD (Radiology Case Reports, 2018)
A 77-year-old woman with liver cirrhosis was admitted to our hospital for marked hemorrhage in her ileal conduit stoma. She had a history of cystectomy and urinary diversion for bladder carcinoma 2 years ago. Contrast-enhanced CT demonstrated varices in the ileal conduit stoma. We accessed the varices via a recanalized paraumbilical vein to avoid pain from the transhepatic approach, and selectively embolized the varices with N-butyl cyanoacrylate (NBCA). We consider antegrade embolization of ileal conduit stomal varices with NBCA to be effective and feasible. Access via a paraumbilical vein is a useful alternative to the transhepatic approach. Keywords: Ectopic varix, Portal hypertension, Embolization, N-butyl cyanoacrylate, Paraumbilical vein